TANGGUNG JAWAB PIDANA PELAKU TINDAK KEJAHATTAN SEKSUAL TERHADAP ANAK (Studi Putusan Nomor 171/Pid.Sus/2020/PN.Ckr): TANGGUNG JAWAB PIDANA PELAKU TINDAK KEJAHATAN SEKSUAL TERHADAP ANAK (Studi Putusan Nomor 171/Pid.Sus/2020/PN.Ckr) - Pettanase, Ismail; Rani, Febrina; fakhriah, syahriati (Legalita, 2023)
Children are a blessing bestowed upon humanity by the divine. As such, they require vigilant safeguarding, nurturing through appropriate and compassionate means. This is because children possess an inherent dignity and entitlements that must be respected, upheld and defended. This research examines sexual violence committed against minors, comparing two court decisions. Court Decision 171/Pid. us/2020/PN. kr involved an adoptive father engaging in sexual acts with his adopted daughter. Court Decision 10/Pid. usAnak/2017/PN Jmb involved an individual having sexual relations with a minor without prior acquaintance, based solely on attraction to the opposite sex. The observe objectives to decide the idea for the judge's considerations and determinations of criminal liability. The analysis methodology selected in its discussion is normative or library legal research. Two approaches are taken: first, a Legislation approach; and second, a Case Approach.The discussion concludes that in sentencing the perpetrators of child sexual violence in Court Decision 171/Pid. us/2020/PN. kr and Court Decision Number 10/Pid. usAnak/2017/PNJmb, the judge's legal considerations were based on properly judging the basis for deciding, societal values, and juridical aspects including the public prosecutor's indictment, witness testimony, defendant testimony, evidence, violated articles, and a Community Supervision Report.